Altered mast cell activity in response to rhinovirus infection provides novel insight into asthma. (3rd May 2020) - Liu, Haiwen; Tan, Jingyu; Liu, Jingfang; Feng, Huiquan; Pan, Dianzhu
Abstract: Objective : Human rhinoviruses (RVs) are a type of common respiratory virus capable of inducing an asthma attack. Although mast cells are important effector cells involved in allergic disease, little is known about the direct effects of an RV infection on mast cells. The aim of this study is to investigate mast cell behavior in response to RV infection and gain insight into the effects of RVs on mast cells. Methods : Viral replication, cell viability, apoptosis and cytokine release were quantified in Human mast cell-1 (HMC-1) cells following RV16 infection. Results : The results revealed that the viral RNA copy number increased substantially over time. Intercellular cell adhesion molecule-1 (ICAM-1) transcripts were significantly upregulated from 1.79 to 6.37 times following RV16 infection compared to the controls ( p ≤ 0.05). Lactate dehydrogenase (LDH) activity was significantly increased, whereas the cell viability decreased following RV16 infection. Examination of the early cellular response to infection revealed that RV16 increased caspase 3 activity and aggravated apoptotic responses. Furthermore, detection of the innate immune response to RV infection revealed that the release of IL-6, IL-8, TNF-α, and IFN-α by HMC-1 cells increased significantly compared to the control groups. Conclusions : RV infection influences mast cell functionality and promotes the innate immune response of mast cells following viral infection. These results provide a novel insight which mast cells have the potential to be involved in the pathogenesis of RV-induced exacerbations of asthma.